Criteria for trauma team activation and staffing requirements for the management of patients with (suspected) multiple and/or severe injuries in the resuscitation room– a systematic review and clinical practice guideline update. - Kühne, Christian Alexander; Weise, Alina; Könsgen, Nadja; Schweigkofler, Uwe; Kaltwasser, Arnold; Pelz, Sabrina; Becker, Tobias; Spering, Christopher; Wagner, Frithjof; Bieler, Dan (European Journal of Trauma & Emergency Surgery, 2025)
Purpose: Our aim was to update the evidence-based and consensus-based recommendations on criteria for trauma team activation (TTA) and staffing requirements for the management of patients with (suspected) multiple and/or severe injuries in the resuscitation room on the basis of available evidence. This guideline topic is part of the 2022 update of the German Guideline on the Treatment of Patients with Multiple and/or Severe Injuries. Methods: MEDLINE and Embase were systematically searched to August 2021. Further literature reports were obtained from clinical experts. Randomised controlled trials, prospective cohort studies, cross-sectional studies and comparative registry studies were included if they compared criteria for identifying severely injured patients requiring trauma team activation or different staffing components (e.g. team composition, training) for the management of patients with (suspected) multiple and/or severe injuries in the resuscitation room. We considered patient relevant outcomes such as mortality as well as prognostic accuracy outcomes. Risk of bias was assessed using NICE 2012 checklists. The evidence was synthesised narratively, and expert consensus was used to develop recommendations and determine their strength. Results: Twenty-one new studies were identified. Potential trauma team activation criteria included vital signs (e.g. systolic blood pressure), type and extent of injury (e.g. central gunshot wound), mechanism of injury (e.g. traffic accident), interventions (e.g. chest tube), specific criteria for geriatric patients, and combined criteria (N = 20). Staffing requirements for the resuscitation room included specific training for orthopaedic trainees (N = 1). Two recommendations were modified, and six additional recommendations were developed. All but two recommendations achieved strong consensus. Conclusion: The key recommendations address the following topics: inter-professional trauma teams in the resuscitation room; trauma team activation for geriatric patients; and trauma team activation criteria based on physiological, anatomical, interventional, and mechanism of injury parameters.